Analysis and Rental of Boarding House Information System In Tangerang City - Stefunus Kristianto (Komunitas Dosen Indonesia, 2022)
For remote workers, overseas students, who have business outside the city, the need for a boarding house is very important to stay for a long time at an affordable cost. Looking for a boarding house can be done by asking friends, owners of nearby boarding houses or visiting adjacent areas from the area visited, so that the information obtained by kostan seekers is less efficient and effective, this results in a lack of information obtained and not fitting according to the ability of the pocket. The purpose of this system can provide data containing kostan information, which is packaged in detail, complete with the location of the boarding house and available facilities. In building this system using PHP and MySQL. Here using the waterfall methodology, this method of logging runs gradually through having to wait for the completion of the previous stage and walks down from the beginning of the development of the system starting from the planning to the final part of the system development is the maintenance stage. The result is a website that contains available boarding house information to make it easier for customers to choose the boarding house they want, and this website can make customers as boarding house owners can promote or add their boarding houses on this website, on this website can also make rental transactions which makes it easier for customers from outside the city to make transactions anywhere and anytime.